[ActionScripting in Flash MX] - Kerman, Phillip (Indianapolis, Ind. : New Riders, 2002)
A guide to ActionScripting using Flash MX. The text provides practical exercises to build problem-solving skills, foundation knowledge in programming, and debugging techniques. The web site companion features downloadable scripts.
pt. I. Foundation. 1. Flash Basics. 2. What's New in Flash MX. 3. The Programmer's Approach. 4. Basic Programming in Flash. 5. Programming Structures. 6. Debugging. 7. The Movie Clip Object. 8. Functions. 9. Manipulating Strings. 10. Keyboard Access and Modifying Onscreen Text. 11. Arrays. 12. Objects. 13. Homemade Objects. 14. Extending ActionScript. 15. Components. 16. Interfacing with External Data -- pt. II. Workshops. pt. IIA. Basic Workshops. 1. Ensuring That Users Have the Flash Player 6. 2. Creating Custom Cursors. 3. Creating a Horizontal Slider. 4. Building a Slide Show. 5. Mapping and Scripted Masks. 6. Working with Odd-Shaped Clickable Areas. 7. Adapting Built-In Components.
Includes index.
Electronic reproduction.
Made available through: Safari Books Online, LLC.
Keywords: ActionScript (Computer program language); Flash (Computer file); Computer animation; Web sites -- Design